The Determinants Of Family Entrepreneurship In The Region Of Bejaia - Bouzit, Naima; Ghanem, Yasmina (جامعة الوادي University of Eloued, 2024)
The aim of this article is to identify the determinants of family business creation. To do this, we carried out a questionnaire survey of 50 SMEs in the region of Bejaia. To identify the characteristics of the companies and entrepreneurs, and also the determinants of family business creation, we proceeded with a descriptive analysis of the survey results, followed by a principal component analysis. Our results show that the family plays a decisive role in business creation. It is in first position, followed by sources of initial finance.
Keywords: Entrepreneurship; family business; determinants; Bejaia